EFEKTIVITAS SUHU DAN LAMA PERENDAMAN BIBIT EMPAT KULTIVAR BAWANG MERAH (Allium cepa L. Kelompok Aggregatum) PADA PERTUMBUHAN DAN DAYA TANGGAPNYA TERHADAP PENYAKIT MOLER - , ENI KAENI; , Ir. Toekidjo, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Moler caused by Fusarium oxysporum f.sp. cepae, one of fungal diseases that infects bulb of shallot. The presence of this pathogen is highly destructed, so that to decrease the impact of moler disease it urgently required to preventing the spread and contamination of the disease especially on the planting fields. The aim was to find the best bulb soaking treatment .The research was conducted at the glass house of Agriculture Faculty, Gadjah Mada University, Yogyakarta, from February to June 2013. The research used dual factor arranged in Completely Randomized Design (CRD). The factors were (1) four cultivars areâTironâ, âCrokâ, âTrisulaâ, and âKuningâ and (2) Soaking bulb treatment